STUDY OF FRUITS MORPHOLOGICAL FEATURES FOR 33 SPECIES BELONG TO CRUCIFERAE FAMILY IN IRAQ - & Al-Masoudi, Al-Dobaissi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The research was aimed to identify fruits morphological characteristics of 33 taxa belonging to the Lepidieae tribe from Brassicaceae. The characteristics of the fruit’s general shape, apex shape, dimensions, colors, surface ornamentation, and beak were determined, the results indicated the importance of each of those characters in isolated species, In general, all the tribe’s fruits were open capsule and short silicula. According to the dimensions of fruit, three species can be distinguished as a group with dimensions greater than 20mm, as in Brossardia, Coluteocarpus, and Didymophysa, and depending on the shape, it was possible to differentiate the species within this group, while the other species were less than 20 mm. in dimensions. They were distinguished by the general shapes, as the fruits of the Aethionema species were distinguished by their winged shaped, whereas the fruits of the genus Biscutella are bi-lobed, and the fruits have an inverted semi-triangular shape in the Capsella and peltate with prominent veins in the genus Horwoodia, or maybe peltate and longitudinally splintered with dark veins in Iberis, while the genus Sameraria fruit is circular to semi-circular characterized by intermediate appendages, while the individuals of the genus Isatis have linear-oblong fruits, and the species of both genus Lipidium and Hymenolobus were distinguished by their small and elliptic fruits and could be differentiated according to other fruits features. So could be conclude the importance of the characteristic of the general shape of the fruit firstly in species isolation then size, ornamentation, and some other traits.